Theory of Mind in Children With Specific Language Impairment: A Systematic Review and Meta‐Analysis. Issue 1 (19th November 2015) - Nilsson, Kristine Kahr; de López, Kristine Jensen
Abstract : The relation between language and theory of mind (ToM) has been debated for more than two decades. In a similar vein, ToM has been examined in children with specific language impairment (SLI), albeit with inconsistent results. This meta‐analysis of 17 studies with 745 children between the ages of 4 and 12 found that children with SLI had substantially lower ToM performance compared to age‐matched typically developing children ( d  =   .98). This effect size was not moderated by age and gender. By revealing that children with SLI have ToM impairments, this finding emphasizes the need for further investigation into the developmental interface between language and ToM as well as the extended consequences of atypical language development.